2012
DOI: 10.1111/j.1532-5415.2012.04058.x
|View full text |Cite
|
Sign up to set email alerts
|

The Elder‐Friendly Emergency Department Assessment Tool: Development of a Quality Assessment Tool for Emergency Department–Based Geriatric Care

Abstract: This study provides preliminary evidence of the validity of three subscales of the proposed elder-friendly ED assessment tool. Results suggest that ED size should be considered in interpreting these subscales. Further evaluation and validation of the proposed tool will be needed to further its utility in helping to focus the quality improvement efforts of clinicians, managers, and administrators related to the care they provide older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 26 publications
7
27
0
Order By: Relevance
“…The consensus as to incorporating a satisfaction evaluation of the elderly in the care provided by the ES is consistent with other studies (10,14) . Satisfaction is an indicator of the quality of the care and, for elderly people, this is related to better results in planning the discharge.…”
Section: Agreement With the Statement: It Is Necessary To Establish Psupporting
confidence: 73%
See 2 more Smart Citations
“…The consensus as to incorporating a satisfaction evaluation of the elderly in the care provided by the ES is consistent with other studies (10,14) . Satisfaction is an indicator of the quality of the care and, for elderly people, this is related to better results in planning the discharge.…”
Section: Agreement With the Statement: It Is Necessary To Establish Psupporting
confidence: 73%
“…The questionnaire was divided into two parts. The first had questions related to information about the participants, and the second part was prepared considering national and international recommendations and criteria necessary for improving the care for the elderly in the ES (5)(6)(9)(10)(11) . The questionnaire contained 35 structured questions in four sections based on the central dimensions of an Elder-Friendly Hospital (6) : social climate; policies and procedures; care systems and processes; and physical design.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9][10][11][12] A number of these interventions have positive effects on important health outcomes, including physical and cognitive function, or reduce subsequent health care use. 7,8,[13][14][15] Broad implementation of such interventions may be a necessary step in optimizing health outcomes for older ED patients, but these efforts may not be sufficient.…”
mentioning
confidence: 99%
“…Papers were selected on the basis of their relevance to developing competencies in GEM by agreement between a geriatrician and an emergency physician. A range of articles including North American initiatives to develop a GEM curriculum and recent reviews and key articles in the field were identified and used to inform the development of the domains and items [7][8][9][10][11][12][13][14][15][16][17] . The development focused upon the additional competencies over and above that which would be expected from training in either geriatric medicine or emergency medicine -so this was not simply a reproduction of how to practice emergency medicine in older people, but an attempt to develop higher level competencies that will add value to existing curriculae 7 .…”
Section: Review Of the Literaturementioning
confidence: 99%